Harms of Antipsychotics in Children and Young Adults: A Systematic Review Update. (October 2018) - Pillay, Jennifer; Boylan, Khrista; Newton, Amanda; Hartling, Lisa; Vandermeer, Ben; Nuspl, Megan; MacGregor, Tara; Featherstone, Robin; Carrey, Normand
Objective: To update and extend our previous systematic review on first- (FGAs) and second-generation antipsychotics (SGAs) for treatment of psychiatric and behavioral conditions in children, adolescents, and young adults (aged ≤24 years). This article focuses on the evidence for harms. Method: We searched (to April 2016) 8 databases, gray literature, trial registries, Food and Drug Administration reports, and reference lists. Two reviewers conducted study screening and selection independently, with consensus for selection. One reviewer extracted and another verified all data; 2 reviewers independently assessed risk of bias. We conducted meta-analyses when appropriate and network meta-analysis across conditions for changes in body composition. Two reviewers reached consensus for ratings on the strength of evidence for prespecified outcomes. Results: A total of 135 studies (95 trials and 40 observational) were included, and 126 reported on harms. FGAs caused slightly less weight gain and more extrapyramidal symptoms than SGAs. SGAs as a class caused adverse effects, including weight gain, high triglyceride levels, extrapyramidal symptoms, sedation, and somnolence. They appeared to increase the risk for high cholesterol levels and type 2 diabetes. Many outcomes for individual drug comparisons were of low or insufficient strength of evidence. Olanzapine caused more short-term gains in weight and body mass index than several other SGAs. The dose of SGAs may not make a difference over the short term for some outcomes. Conclusions: Clinicians need to weigh carefully the benefit-to-harm ratio when using antipsychotics, especially when treatment alternatives exist. More evidence is needed on the comparative harms between antipsychotics over the longer term.